Compressibility of tableting materials and properties of tablets with glyceryl behenate - Mužíková Jitka; Muchová Sandra; Komersová Alena; Lochař Václav (Acta Pharmaceutica)
The paper studies the compressibility of directly compressible tableting materials with dry binders, spray-dried lactose and microcrystalline cellulose, and glyceryl dibehenate at various concentrations. Compressibility was evaluated by means of the energy profile of compression and tensile strength of tablets. Release rate of the active ingredient, salicylic acid, from the tablets was also examined. In the case of microcrystalline cellulose, a higher concentration of glyceryl dibehenate increased the strength of tablets, while this did not occur in the case of spray-dried lactose. Increasing concentration of glyceryl dibehenate prolonged the release of salicylic acid; however, no statistically significant difference was found compared to the type of the dry binder used